A new systematization of histological analysis for the diagnosis of Hirschsprung's disease (Clinics, 2023)
Background: Hirschsprung's Disease (HD) is characterized by intestinal sub-occlusion and the absence of enteric ganglion cells. A rectal biopsy examination is performed to confirm the diagnosis. In a recent study, we demonstrated that the analysis of 60 sections of rectal mucosa and submucosa stained by H&E may ensure a 90% diagnostic accuracy. Although the need to analyze so many sections makes the process of reading the slides more time-consuming, this encouraged us to study their distribution in the healthy rectal submucosa, to simplify the diagnosis.Objectives: To develop a method that facilitates HD diagnosis by studying the distribution of ganglion cells in the submucosal plexus.Methods: Using the calretinin technique, we studied the distribution of plexuses in 60 fragments of rectal submucosa from 19 cadavers. After the study, the reading method created was used for diagnosis in 47 cases of suspected HD, using H&E staining. The accuracy was verified by comparing the results obtained with H&E to those obtained with the acetylcholinesterase technique, the golden standard in our laboratory.Results: The study of submucosal plexus distribution showed that just by examining the submucosal region every 20 µm, approximately, it is possible to locate a ganglionic plexus, and we have already been able to diagnose HD with 93% accuracy.Conclusion: The study of ganglion cell distribution enabled the creation of a simplified method for reading the slides. The method applied achieved good accuracy and it can be used as an alternative method in HD diagnosis.